Therapeutic drug repositioning with special emphasis on neurodegenerative diseases: Threats and issues - Kakoti, Bibhuti Bhusan; Bezbaruah, Rajashri; Ahmed, Nasima (Frontiers in Pharmacology, 2022)
Drug repositioning or repurposing is the process of discovering new indications for authorized or failed/abandoned molecules for use in different diseases.Thisapproach revitalizes the traditional drug discovery method by revealing new therapeutic applications for existing drugs. There are numerous studies available that highlight the triumph of several drugs as repurposed therapeutics. For example, sildenafil to aspirin, thalidomide to adalimumab, and so on. Millions of people worldwide are affected by neurodegenerative diseases. According to a 2021 report, the Alzheimer's Disease Association estimates that 6.2 million Americans have Alzheimer's disease. By 2030, an estimated 1.2 million people in the United States may have Parkinson's disease.Drugs that act on a single molecular target benefit people suffering from neurodegenerative diseases. Current pharmacological approaches, on the other hand, are limited in their ability to significantly alter the course of the disease and provide patients with inadequate and momentary benefits.Drug repositioning–based approaches appear to be very pertinent, cost- and time-saving strategies for the development of therapeutic opportunities for such diseases in the current era. Kinase inhibitors, for example, which were developed for variousoncology indications, demonstrated significant neuroprotective effects in neurodegenerative diseases.This review shed light on the classical and recent examples of drug repositioning at various stages of drug development, with special focus on the neurodegenerative disorders and the aspects of threats and issues viz. the regulatory, scientific, and economic aspects.